PERUBAHAN KUALITAS AKTA NOTARIS MENJADI AKTA DIBAWAH TANGAN ATAU MENJADI BATAL DEMI HUKUM BERDASARKAN UNDANG-UNDANG JABATAN NOTARIS - Januar, Inri; Siringoringo, Poltak; Saragi, Paltiada (Fakultas Hukum Universitas Kristen Indonesia, 2024)
Based on article 15 paragraph 1 of the Law on the Position of Notaries, article 1313 of the Civil Code and article 1320 of the Civil Code and also the principle of freedom of contract, a notarial deed can also be called an agreement with perfect evidentiary power. The legal consequences that arise if there is a violation in the formation of a notarial deed can be seen from two sides. Firstly, the legal consequences are seen in terms of the formal and material requirements of a notarial deed based on Law on the Position of Notaries Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the Position of Notaries. Of all the legal consequences listed in the UUJN, it only reduces the quality of an authentic notarial deed, turning it into a deed that has the power of proof as a private deed. Second, look at the conditions required in Article 1320 of the Civil Code. If the category of subjective requirements is not fulfilled, the result can be cancelled, which means that the cancellation must be requested before a judge. The category of objective requirements means that if they are not met, the legal consequences will make the agreement null and void. In this way, a notarial deed as an authentic deed can turn into a private deed and can also become null and void. The methodology used is normative with a statutory approach and a conceptual approach. The purpose of this writing is to determine the legal consequences of notarial deeds that are not made in accordance with legal provisions.